2016
DOI: 10.1016/j.mmcr.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Malassezia pachydermatis fungemia in an adult with multibacillary leprosy

Abstract: Malassezia pachydermatis is a relatively rare agent of bloodstream infections. We describe an unusual case of Malassezia fungemia in an adult patient hospitalized for Staphylococcus aureus bacteremia who was also found to have multibacillary leprosy. Treatment of the patient required extensive medical management but resulted in a good outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Once introduced to a facility, Malassezia yeasts can persist on incubator surfaces for prolonged periods of time (Van Belkum et al, 1994). A subsequent case report described a facial granuloma caused by M. pachydermatis in a dog owner (Fan et al, 2006), and recently M. pachydermatisassociated fungemia has been reported in a small number of adults with various predisposing factors (Choudhury and Marte, 2014;Roman et al, 2016;Lee et al, 2019). Since hand contamination by M. pachydermatis is common amongst dog owners, especially in owners of allergic dogs with Malassezia overgrowth (Morris, 2005), there is a clear need for rigorous hand hygiene by individuals in contact with pet dogs and cats, especially when there is contact with immunocompromised individuals (Bond et al, 2020).…”
Section: Potential Transmission Of Malassezia Yeasts From Animals To mentioning
confidence: 99%
“…Once introduced to a facility, Malassezia yeasts can persist on incubator surfaces for prolonged periods of time (Van Belkum et al, 1994). A subsequent case report described a facial granuloma caused by M. pachydermatis in a dog owner (Fan et al, 2006), and recently M. pachydermatisassociated fungemia has been reported in a small number of adults with various predisposing factors (Choudhury and Marte, 2014;Roman et al, 2016;Lee et al, 2019). Since hand contamination by M. pachydermatis is common amongst dog owners, especially in owners of allergic dogs with Malassezia overgrowth (Morris, 2005), there is a clear need for rigorous hand hygiene by individuals in contact with pet dogs and cats, especially when there is contact with immunocompromised individuals (Bond et al, 2020).…”
Section: Potential Transmission Of Malassezia Yeasts From Animals To mentioning
confidence: 99%
“…The genus Malassezia is comprised of 18 lipophilic species characterized as commensal yeasts, which are part of the skin mycobiota of both humans and animals (Nagata et al, 2012;Cabañes, 2014;Cabañes et al, 2016;Honnavar et al, 2016;Prohic et al, 2016), and are commonly located in lipid-rich body areas, such as the scalp, face, and trunk (Gupta et al, 2004;DeAngelis et al, 2005). Some species of this genus have been associated with skin diseases (Gupta et al, 2004;Prohic et al, 2016) and systemic infections (Gaitanis et al, 2012;Kaneko et al, 2012;Nagata et al, 2012;Iatta et al, 2014Iatta et al, , 2018Roman et al, 2016;Lee et al, 2018;Theelen et al, 2018;Chen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Malassezia furfur and Malassezia pachydermatis are two representative species of this genus which are found mainly in the skin of humans and pets such as dogs and cats, respectively (Cabañes, 2014). These two species have been associated with systemic infections in premature infants (Zomorodain et al, 2008;Iatta et al, 2014Iatta et al, , 2018 as well as in low-weight infants with central venous catheters (CVC), parenteral lipid infusions and long hospital stays (Bell et al, 1988;Chang et al, 1998;Gupta et al, 2014), The two species have also been shown to infect immunosuppressed children and adults (Gaitanis et al, 2012;Kaneko et al, 2012;Roman et al, 2016); in fact, in some cases the percentage of fungemia by M. furfur (2.1%) is higher than fungemia by Candida spp. (1.4%) (Iatta et al, 2014), and prevalence can range from 2.1 to 4.4% in a neonatal intensive care unit depending on the diagnostic method (Iatta et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Malassezia is a lipid-dependent genus of yeasts found as commensals on human and animal skin [ 1 , 2 ]. Under specific conditions, these yeasts have been associated with skin diseases [ 3 ], Crohn’s disease, the exacerbation of colitis [ 4 ], Parkinson’s disease [ 5 ], pancreatic ductal adenocarcinoma [ 6 ], and fungemia [ 7 , 8 , 9 ] ( Table 1 ). Factors determining the outcome of host–microbe interactions are multifactorial, involving environmental conditions like temperature and humidity, but also host factors and the predisposition of the host, which may be related to genetic factors and impairment in the immune response [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%